Development of a national stock market in Lesotho : a response to structural challenges. - Tau, Puseletso Marealeboha Theresia (My University, 2016)
This study examines the determinants of stock market development in a broader sense, in an effort to investigate the positive or negative impact they can have on the establishment of the national stock market in Lesotho. The focus is on the benefits enjoyed by other African countries from the establishment of stock markets, in particular, in Sub-Saharan Africa, whose effects can also be enjoyed by the Lesotho economy. I have concluded that Lesotho can also benefit from the establishment of a stock market and reforms to strengthen the institutional infrastructure are essential.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Finance and Investment), 2016
Keywords: Stock exchanges--Lesotho; Investments--Lesotho; Capital market--Lesotho